MOTIVASI BEKERJA PADA CHEF PRIA - Faradita, Kirana (EMPATHY Jurnal Fakultas Psikologi, 2013)
ABSTRACT This study aims to find the motivation to work on male chef. This study was conducted in Jakarta. Respondents in the study were two men who worked in the culinary field in Jakarta. The research method that was used is a qualitative research method with the type of case study. Data was collected by semi- structured interviews and observations with the respondents. The results showed that the respondents have a high motivation to be a chef. The interest of the respondent to be chef there since childhood as a hobby cook and cook often see family members. Growing both more serious and learn more about the culinary world with the path in vocational education and hospitality majors diploma cookery. After graduation they worked as a chef at one of the food companies in Jakarta. Opportunities as chef considerable and substantial income to be one of the factors that influence both the desire to work as a chef.Keywords : work motivation and chef.